Timbre transfer of classical guitars using impulse response and a laser displacement sensor - Yeh, Che-Hsu; Chen, Chii-Chang (Sound & Vibration, 2026)
Conventional characterization of musical instruments relies on microphones, whose measurements depend strongly on distance, sound radiation directionality, and the non-uniform frequency responses of microphones and preamplifiers, often introducing distortions. Laser displacement sensors, widely used for vibration and surface measurements, offer a higher maximum displacement–to–resolution ratio than laser Doppler vibrometry. Measuring instrument vibrations with such sensors enables the capture of a more intrinsic acoustic source. This study demonstrates timbre transfer from a hand-made guitar to a José Ramírez guitar using convolution with impulse responses obtained from both a laser displacement sensor and a microphone. Timbre similarity is evaluated via cross-correlation of acoustic spectra between original and transferred notes. For 33 notes (E2–C5), the laser-based method yields higher cross-correlation in 28 cases compared to the microphone-based approach. The results highlight the distinction between vibration-based and pressure-based timbre characterization. Microphone measurements capture far-field sound pressure along with environmental noise, whereas laser displacement sensing directly reflects the instrument’s vibrational behavior. Consequently, laser-based impulse responses provide a more intrinsic representation of acoustic spectra and enable more accurate timbre transfer. After recording a performance, the timbre of one instrument can therefore be transferred more precisely to another using impulse responses derived from laser displacement sensors.